PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND CLUB TERHADAP HASIL BELAJAR IPS SISWA KELAS V SDN GUGUS III GUNUNGSARI TAHUN PELAJARAN 2018/2019 - Nurliawati Nurliawati; Nurhasanah Nurhasanah; Awal N. K Rosyidah; Muhamad Tahir (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2021)
This study aims to determine whether or not there is an effect of the Round Club type cooperative learning model on social studies learning outcomes for fifth graders at SDN cluster III Gunungsari in the 2018/2019 school year. This study uses a quantitative experiment, the type of Quasi Experimental Design, the type of Noneequivalent Control Group Design. The population of this study were all fifth grade students of SDN cluster III Gunungsari. The sampling technique used was purposive sampling with samples from SDN 3 Midang and SDN 2 Kekeri. The data collection technique in this study used a learning implementation observation sheet and a cognitive learning outcome test (pretest-posttest). The data from the observation of the implementation of learning using the Round Club learning model were analyzed using descriptive analysis, namely the implementation of learning during two meetings reached 100% (very good). Cognitive learning outcomes data (pretest-posttest) were analyzed using analysis of covariance (ANACOVA), the value was 0.000 < 0.05 and the average corrected in the experimental class was 85,041 > 66,479 in the control class. This shows that Ho is rejected and the research hypothesis is accepted which reads that there is an effect of the Round Club type cooperative learning model on social studies learning outcomes for fifth grade students of SDN cluster III Gunungsari in the 2018/2019 school year. The results of the Estimates of Effect Size analysis with Partial Eta Squared show that the difference in student learning outcomes between the experimental class and the control class of 50.6% is influenced by the Round Club learning model. While the remaining 49.4% is influenced by other factors. the use of the Round Club learning model in learning can improve student learning outcomes, therefore it is recommended to use the Round Club learning model in the world of education.